2011
DOI: 10.1007/s11631-011-0530-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in sulfur isotopic composition of dissolved SO4 2− in the Aha Lake, Guiyang and their implications

Abstract: The Aha Lake is a seasonal anoxic water system in the southwest of Guiyang City, Guizhou Province, China. Seasonal variations in SO 4 2-concentrations and their isotopic compositions in lake water as well as in the tributaries were investigated in this study. The results showed that sulfate concentrations in river water range from 0.94 to 6.52 mmol/L and their δ 34 S values range from -14.9‰ and 0.9‰, while lake water has sulfate concentrations ranging from 1.91 to 2.79 mmol/L, and δ 34 S values from -9.8‰ to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The isotopic composition of sulfate above 7 m depth was similar to the isotopic composition of sulfate in rainwater ( Fig. 2B; δ 34 S rainwater = -7‰; Song et al, 2011). The constant concentrations and δ 34 S value of -10.5‰ ± 2.1‰ between 7 and 20 m water depth are consistent with coal-derived sulfate, the main source of sulfate to the lake (δ 34 S coal = -12‰; Song et al, 2011).…”
Section: Decoupling Between Sulfur Isotope Composition In the Water Csupporting
confidence: 65%
See 1 more Smart Citation
“…The isotopic composition of sulfate above 7 m depth was similar to the isotopic composition of sulfate in rainwater ( Fig. 2B; δ 34 S rainwater = -7‰; Song et al, 2011). The constant concentrations and δ 34 S value of -10.5‰ ± 2.1‰ between 7 and 20 m water depth are consistent with coal-derived sulfate, the main source of sulfate to the lake (δ 34 S coal = -12‰; Song et al, 2011).…”
Section: Decoupling Between Sulfur Isotope Composition In the Water Csupporting
confidence: 65%
“…2B; δ 34 S rainwater = -7‰; Song et al, 2011). The constant concentrations and δ 34 S value of -10.5‰ ± 2.1‰ between 7 and 20 m water depth are consistent with coal-derived sulfate, the main source of sulfate to the lake (δ 34 S coal = -12‰; Song et al, 2011). An increase in δ 34 S sulfate and the presence of sulfide below 22 m depth indicates that microbial sulfate reduction was active within the water column.…”
Section: Decoupling Between Sulfur Isotope Composition In the Water Cmentioning
confidence: 99%
“…Previous investigation showed that seasonal thermal stratification existed in Aha Reservoir normally from June to October [ 10 , 13 ]. As shown in Fig 3 , there is thermal stratification in September and no stratification in March.…”
Section: Resultsmentioning
confidence: 99%
“…An anoxic hypolimnion is developed as a result of a stratification regime and causes notable changes in the water quality of the hypolimnion. It is well known that water below the thermocline is normally depleted of dissolved oxygen, and contains high concentrations of SO 4 2- and hydrogen sulfide produced during the process of anaerobic decomposition, and elevated levels of metals such as iron and manganese brought into solution from the bottom sediments as a result of the strong reducing conditions [ 1 , 8 , 10 , 19 ]. The water discharged from the reservoir hypolimnion to the culvert and discharge pipe is markedly anoxic and enriched in sulfur during June-October (Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation